Observing Ocean Conditions: Prior and Post Cyclone ‘Tauktae’ Using Satellite and In-situ Data - Kesavakumar Balakrishnan; Suchandra Aich Bhowmick; Venkatesan Ramasamy; Shanmugam Palanisamy; Ram Kumar Giri; M. Jishad; Anup Kumar Mandal; M. Seemanth; Rishi Gangwar; Neeraj Agarwal; Rashmi Sharma; Sundar Ranganathan; et al. (Journal of the Indian Society of Remote Sensing, 2026)

Ensemble-based data assimilation to improve wind-wave field in the Bay of Bengal - Tharani A.; Sannasiraj S. A.; Balaji C.; Seemanth M.; Suchandra Aich Bhowmick (Ocean Dynamics, 2025)

SARAL/AltiKa–An Unprecedented Journey for Monitoring Global Sea Levels and Serving Ocean Applications - Suchandra A. Bhowmick; Aditya Chaudhary; M. Seemanth; Smitha Ratheesh; K. M. Sreejith; V. P. Krishna; P. G. Remya; Imranali M. Momin; Honey Gupta; J. V. Thomas; Neeraj Agarwal; Rashmi Sharma; et al. (Journal of the Indian Society of Remote Sensing, 2025)

Assessing the Influence of EOS-06 Scatterometer Winds on Indian Ocean Wave Predictions with Unstructured WAVEWATCH III - Remya P. G.; Roshyal Joy; Seemanth M.; Abhisek Chakraborty; Anuradha Modi; N. Kameshwari (Journal of the Indian Society of Remote Sensing, 2025)

Impact of assimilating satellite and in-situ buoy observed significant wave height on a regional wave forecasting system in the Indian Ocean - M Seemanth; P G Remya; Raj Kumar; Arun Chakraborty (Journal of Earth System Science, 2024)

Characterization of internal solitary waves in the Andaman Sea and Arabian Sea using EOS-04 and sentinel observations - Anup Kumar Mandal; M. Seemanth; Ramakrishnan Ratheesh (International Journal of Remote Sensing, 2024)

How useful are mispointing phase SARAL/AltiKa geophysical products for ocean applications? - Suchandra Aich Bhowmick; Aditya Chaudhary; M. Jishad; M. Seemanth; Utkarsh; Neeraj Agarwal; Rashmi Sharma; Honey Gupta; J.V. Thomas; Pascal Bonnefond; J. Verron (Advances in Space Research, 2024)

A pathway for multi-stage cyclone-induced hazard tracking—case study for Yaas - Atul Kumar Varma; Neeru Jaiswal; Ayan Das; Mukesh Kumar; Nikhil V. Lele; Rojalin Tripathy; Saroj Maity; Mehul Pandya; Bimal Bhattacharya; Anup Kumar Mandal; M. Jishad; M. Seemanth; et al. (Natural Hazards, 2023)

SAtellite-based Marine Process Understanding, Development, Research and Applications for Blue Economy (SAMUDRA): A Technology Demonstration Program in the Bay of Bengal - Rashmi Sharma; Neeraj Agarwal; Ratheesh R; Surisetty VVArun Kumar; A. D. Rao; KVSR Prasad; Jaya Kumar Seelam; R. Mani Murali; V. Suneel; Surendra Singh K; R. K. Sarangi; Soba J. Kizhakudan; et al. (Journal of the Indian Society of Remote Sensing, 2023)

Techno-economic Analysis of Wave Energy Resource for India - Ravi P. Patel; Garlapati Nagababu; Surendra Singh Kachhwaha; V. V. Arun Kumar Surisetty; M. Seemanth (Journal of the Indian Society of Remote Sensing, 2023)

Analysis of SARAL/AltiKa Wind and Wave over Indian Ocean and its Real-time Application in Wave Forecasting System at ISRO - Suchandra Aich Bhowmick; Ruchi Modi; K. G. Sandhya; M. Seemanth; T. M. Balakrishnan Nair; Raj Kumar; Rashmi Sharma (Marine Geodesy, 2015)

On the spatial structure and time evolution of shamal winds over the Arabian Sea – a case study through numerical modelling - K. Vinod Kumar; M. Seemanth; P. Vethamony; V. M. Aboobacker (International Journal of Climatology, 2014)
Shamal events are extra‐tropical weather systems which occur in winter (cold and dry winds) as well as summer (hot and humid winds) with strong northwesterly or northerly winds blowing over the Arabian Peninsula. We have used Weather Research and Forecasting ( WRF ) model to simulate a major winter shamal event (having duration of 3–5 days), which occurred in 2008 and analysed the spatial structure and time evolution of shamal winds over the Arabian Sea ( AS ). The study reveals that horizontally, shamal winds extend upto 14°N and bring out significant changes in the atmospheric temperature—longitudinally from Arabian coast to west coast of India; its vertical extension is upto to approximately 8 km near Oman and approximately 3 km near Ratnagiri coast. Along the Arabian coast a temperature drop of 12 °C is observed and along west coast of India a drop of 5 °C. It gets dissipated when northeast monsoon winds dominate. Its speed reduces from 15 m s −1 (Oman coast) to 9 m s −1 (central AS ) as it propagates into AS . However, it must be noted that the present work is limited to a case study and hence, the southerly extension of the phenomenon and the associated changes in air temperature should not be considered a climatological reference. The shamal events may influence the wind induced circulation, heat flux and stratification in the AS , and these need to be analysed further.